Brief Report: The Prevalence of Neurofibromatosis Type 1 among Children with Autism Spectrum Disorder Identified by the Autism and Developmental Disabilities Monitoring Network - Bilder, Deborah A.; Bakian, Amanda V.; Stevenson, David A.; Carbone, Paul S.; Cunniff, Christopher; Goodman, Alyson B.; McMahon, William M.; Fisher, Nicole P.; Viskochil, David (Journal of autism and developmental disorders, 2016)
Neurofibromatosis type 1 (NF1) is an inherited neurocutaneous disorder associated with neurodevelopmental disorders including autism spectrum disorder (ASD). The frequency of ASD/NF1 co-occurrence has been subject to debate since the 1980s. This relationship was investigated in a large population-based sample of 8-year-old children identified with ASD (N = 12,271) by the Centers for Disease Control and Prevention’s Autism and Developmental Disabilities Monitoring (ADDM) Network. Twenty-two (1-in-558) children with ASD had diagnosed NF1, exceeding NF1 general population estimates by four to five fold. Children with ASD/NF1 versus ASD without NF1 were significantly less likely to receive a community-based ASD diagnosis ( p = 0.04) and understand non-verbal communication ( p = 0.001). These findings underscore the importance of including social-communication ability among relevant developmental concerns in children with NF1.